Efeitos dos agonistas canabinoides, WIN 55 212-2 e ACEA, na atividade antitumoral da oxaliplatina e na neuropatia sensitiva periférica associada em camundongos com tumor de células ct26.wt - Carvalho, Victor Machado (2024)
Oxaliplatin (OXL), a 3rd generation platinum compound used in the adjuvant chemotherapy of colorectal cancer (CRC; 2nd place in incidence in Brazil), which is extremely important in clinical oncology, has the main adverse effect of peripheral sensory neuropathy (PSN), a debilitating and painful neurotoxic condition that can lead to treatment suspension or dose reduction, thus reducing the survival of patients with CRC. Studies have shown that the endocannabinoid system is capable of modulating the nociceptive pathway and that cannabinoid derivatives are capable of preventing the neurotoxic damage of OXL. However, their effect has not yet been evaluated in animals with RCC cell tumors to see if they interfere with OXL's antitumor potential. Therefore, the aim of this study was to evaluate the effect of cannabinoid agonists on the antitumor effect of OXL and NSP associated with this chemotherapy in animals with CT26.WT cell tumors. Male Balb/c Specific Pathogen Free (SPF) mice were inoculated with CT26.WT cells and, after detecting a palpable tumor mass, treated with WIN-55-2012-2 (non-selective cannabinoid agonist; 1mg/kg) and ACEA (selective CB1 agonist; 3 mg/kg), associated or not with OXL (6mg/kg). Tumor growth was monitored until the 12th day, concomitantly with the evaluation of PNS by the mechanical plantar allodynia (von Frey) and cold allodynia (acetone test) tests. After the protocols were carried out, the animals were euthanized to collect dorsal root ganglion (DRG) and tumor tissue for immunofluorescence for ATF-3, Ki67, CD31, CB1 and CB2. The cytotoxic effect, in vitro, of ascending concentrations of WIN and ACEA and the combination of both with OXL was evaluated by the cell viability assay (Alamar blue). WIN and ACEA inhibited NSP, significantly reducing mechanical and cold allodynia (p<0.05). ATF-3 immunoexpression in DRG was also significantly reduced. Analysis of tumor growth kinetics showed that OXL inhibited tumor growth and that WIN and ACEA alone did not. WIN did not interfere with the effect of OXL, while the ACEA+OXL group showed a significant anti-tumor effect (p<0.05). Marking with CD31 and Ki67 was reduced in the OXL and WIN+OXL/ACEA+OXL groups. There was no difference in the expression of CB1 receptors between the groups, but there was amplification in the expression of CB2 receptors in the groups treated with OXL alone. In vitro, OXL reduced cell viability with IC50=2,2. WIN and ACEA reduced viability with IC50 =5,6 and 56.1, respectively. The combination of OXL+WIN reduced the IC50 to 0.21and the combination ACEA+OXL reduced the IC50 to 0.01indicating synergism. WIN and ACEA showed antineuropathic effects and in vivo did not interfere with the antitumor effect of OXL. WIN reduced cell growth in vitro, but not in vivo, and increased the effect of OXL in vitro. ACEA, combined with OXL, reduced tumor growth in vivo and in vitro. The results are promising and suggest further investigation of cannabinoid agonists as adjuvants in OXL therapy.